2007
DOI: 10.1111/j.1742-4658.2007.06000.x
|View full text |Cite
|
Sign up to set email alerts
|

Helicases − feasible antimalarial drug target for Plasmodium falciparum

Abstract: Of the four Plasmodium species that cause human malaria, Plasmodium falciparum is responsible for the most severe form of the disease and this parasite is developing resistance to the major antimalarial drugs. Therefore, in order to control malaria it is necessary to identify new drug targets. One feasible target might be helicases, which are important unwinding enzymes and required for almost all the nucleic acid metabolism in the malaria parasite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 43 publications
0
37
0
Order By: Relevance
“…12 Recently we have also reported that helicases could be used as feasible drug targets for the control of malaria. 13 Given the importance of helicases in parasite growth and survival and in order to obtain further information on helicases in the P. falciparum genome, we have carried out a genome wide analysis of helicases using the bioinformatics approach. We report the detailed information on almost all the helicases from P. falciparum and a comparison of these with the human host.…”
mentioning
confidence: 99%
“…12 Recently we have also reported that helicases could be used as feasible drug targets for the control of malaria. 13 Given the importance of helicases in parasite growth and survival and in order to obtain further information on helicases in the P. falciparum genome, we have carried out a genome wide analysis of helicases using the bioinformatics approach. We report the detailed information on almost all the helicases from P. falciparum and a comparison of these with the human host.…”
mentioning
confidence: 99%
“…This is the first description involving a protein of the DEAD box family of RNA helicase in any filarial species. RNA helicases have been identified as potential drug target candidates in herpes simplex virus (HSV), hepatitis C virus (HCV), and malarial parasites (Tuteja 2007;David 2003); however, they have not yet been explored in filarial nematodes. Immunoscreening of cDNA expression libraries and phage display libraries using patients' sera especially from endemic normal or monoclonal antibodies (Gnanasekar et al 2004) is one of the most sought after approaches in the search for filarial vaccine candidates/drug targets (Rao et al 2000;Kobayashi et al 2007;Shibuia et al 2001;Feng et al 2007;Nisbet et al 2008;Merriweathera et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…This enzyme is considered a rational target for structure-based molecular design (Tuteja 2007;David 2003). A study on the three-dimensional structure of the protein will shed more light on the important conserved motifs, further revealing the structural features of this protein and its ATP-dependent RNA unwinding property (Christine et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…9 Since helicases play essential roles in the metabolism of DNA and RNA, helicase inhibitors may offer a feasible route towards the development of novel drugs. 10 Recently we have reported the detailed characterization of the DDX19/Dbp5 homolog designated ©2 0 1 1 L a n d e s B i o s c i e n c e .…”
Section: W E Have Recently Reported the Isolation And Characterizatiomentioning
confidence: 99%
“…The effect of these nucleic acid binding agents on inhibition of unwinding of the duplex might have a deleterious effect on further DNA/RNA transaction processes. 10,17 The effective DNA-binding ligands, which inhibited the DNA unwinding and ATPase reactions catalyzed by PfD66 were DAPI, nogalamycin, ethidium bromide and netropsin. An oligopyrrolamidine, netropsin binds to the minor groove of DNA and inhibits WRN and BLM helicases but it did not inhibit E. coli UvrD helicase activity.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%